2017
DOI: 10.1007/s10549-017-4592-y
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab combined with doublet or single-agent chemotherapy as first-line therapy for HER2-positive metastatic breast cancer

Abstract: PurposeTo investigate the efficacy and safety of doublet versus single-agent chemotherapy (CT) plus trastuzumab (H) as first-line therapy for human epidermal growth factor 2 receptor (HER2)-positive metastatic breast cancer (MBC).MethodsWe searched for randomized clinical trials (RCTs) that evaluated the treatment effects of single-agent or doublet CT+H as first-line therapies for HER2-positive MBC. The main outcomes measured for this study included the overall response rate (ORR), progression-free survival (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…We included several new trials [3,5,18,21] that were not included in the previous study [22], in particular studies that included new antitumor drugs including gemcitabine and capecitabine. A meta-analysis [23] included four RCTs with 1,044 participants and found that the combination of doublet chemotherapy with trastuzumab compared with single-agent chemotherapy as first-line therapy for human epidermal growth factor receptor (HER2)-positive MBC is associated with longer PFS and OS, and recommended that doublet chemotherapy appears to be an appropriate regimen for good performance status patients. This meta-analysis with multicentre cohort study findings support PFS and OS benefit of chemotherapy than observation after first-line chemotherapy in MBC.…”
Section: Discussionmentioning
confidence: 99%
“…We included several new trials [3,5,18,21] that were not included in the previous study [22], in particular studies that included new antitumor drugs including gemcitabine and capecitabine. A meta-analysis [23] included four RCTs with 1,044 participants and found that the combination of doublet chemotherapy with trastuzumab compared with single-agent chemotherapy as first-line therapy for human epidermal growth factor receptor (HER2)-positive MBC is associated with longer PFS and OS, and recommended that doublet chemotherapy appears to be an appropriate regimen for good performance status patients. This meta-analysis with multicentre cohort study findings support PFS and OS benefit of chemotherapy than observation after first-line chemotherapy in MBC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies on single-agent vs. double-agent chemotherapy combined with trastuzumab for the treatment of HER2-positive MBC had mixed results ( 48 ). To resolve this contradiction, a meta-analysis by Yu et al ( 49 ) showed that the PFS and OS of patients with HER2-positive MBC treated with dual-drug chemotherapy combined with trastuzumab were better, but the treatment-related toxicity was more severe. BCLM can cause liver function damage, so the scope of application of dual-drug chemotherapy combined with trastuzumab needs to be explored in relevant clinical trials.…”
Section: Treatment For Bclmmentioning
confidence: 99%